1964
DOI: 10.1037/h0045135
|View full text |Cite
|
Sign up to set email alerts
|

Changes in moral judgment and self-acceptance in college students as a function of companionship with hospitalized mental patients.

Abstract: The present investigation describes studies undertaken to determine the effects of association with hospitalized mental patients on the personalities of 32 male college students who were compared to a control group of 24 comparable students who had not been involved in this experience with mental patients. The former demonstrate significant positive change in self-acceptance and in moral judgments concerning sexual and aggressive behaviors. The nature of the companionship experience is examined in order to elu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0

Year Published

1973
1973
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 4 publications
3
19
0
Order By: Relevance
“…In fact, we have obtained preliminary evidence that people are changed by their experiences as AIDS volunteers (see also Holzberg, Gewirtz, and Ebner, 1964;King, Walder, and Pavey, 1970;Scheibe, 1965). Respondents in our national survey reported on how they perceived their attitudes had changed as a consequence of volunteering and how volunteering had affected their lives.…”
Section: Extending Volunteer Servicementioning
confidence: 87%
“…In fact, we have obtained preliminary evidence that people are changed by their experiences as AIDS volunteers (see also Holzberg, Gewirtz, and Ebner, 1964;King, Walder, and Pavey, 1970;Scheibe, 1965). Respondents in our national survey reported on how they perceived their attitudes had changed as a consequence of volunteering and how volunteering had affected their lives.…”
Section: Extending Volunteer Servicementioning
confidence: 87%
“…In at least nine studies, personality measures were administered either at the request of staff persons associated with the volunteer agency (Beckman, 1972;Smith and Nelson, 1975) or by presumably independent researchers who carried out their studies within the volunteer agency setting (Cowen, Zax, and Laird, 1966;Pretz, 1979;Hersch, Kulik, and Scheibe, 1969;Holzberg, Gewirtz, and Ebner, 1964;Jamison and Johnson, 1975;Sakowitz and Hirschman, 1975;Tapp and Spanier, 1973). In at least nine studies, personality measures were administered either at the request of staff persons associated with the volunteer agency (Beckman, 1972;Smith and Nelson, 1975) or by presumably independent researchers who carried out their studies within the volunteer agency setting (Cowen, Zax, and Laird, 1966;Pretz, 1979;Hersch, Kulik, and Scheibe, 1969;Holzberg, Gewirtz, and Ebner, 1964;Jamison and Johnson, 1975;Sakowitz and Hirschman, 1975;Tapp and Spanier, 1973).…”
Section: Methodological Issuesmentioning
confidence: 99%
“…There have been several studies on college volunteers that typically focus on their personality traits (Chinsky 1969;Carkhuff and Truax 1966;Cowen et al 1966;Holzberg et al 1964;Gelineau and Kantor 1969;as cited in Hobfoll 1980). Trudeau and Devlin (1996) examined volunteer students in comparison with non-volunteer students, where they found significant results for their hypotheses for female volunteers, and also found that on the whole, students were more motivated by altruistic reasons.…”
Section: Study Objectivesmentioning
confidence: 98%